Interacción Genotipo – Ambiente de híbridos triples experimentales de maíz (zea mays l.), en dos zonas del litoral Ecuatoriano. - Quimí Villanueva, Dario (2015)
This research was conducted in the town of Quevedo at the Experimental Farm "La María" and Balzar on Campus "The Guayaquil" the grounds of the Agricultural Association The Rula. The overall objective of this study was to: determine the behavior, adaptability and handling of promising hybrids maize triples that lead to improve the profitability of producers, and the specific objectives were: 1) Determine the ambient genotype maize hybrids promising interaction. 2) Evaluate the grain characteristics of the experimental hybrids obtained from single crosses. The five experimental hybrids were studied and promising (SM45 X SSD08) SV39 (SV35 SM45 X) SV39 (SM45 X SV 15) SV39 (SV15 X SM45) SV39 (SM15 X SSD08) SV39 and H-commercial lNlAP 551, AG-003 and H-553 lNlAP (control), which corresponded to the treatments under study in areas of Quevedo and Balzar. Area was used for each experimental design Randomized Complete Blocks. Tukey test at 95% was used to establish The statistical differences between the means of the hybrid and the "t" test to determine the statistical differences between the zones. The variables male and female flowering, plant height and ear position, diameter, length and number of rows per ear, diseases, grain yield were evaluated. ...